Language, gender and law in the Judaeo-Islamic milieu. - Ashur, Amir, 1966-; Stampfer, Y. Zvi, (Études sur le judaïsme médiéval;, 2020)
"The articles in this volume focus on the legal, linguistic, historical and literary roles of Jewish women in the Islamic world of the Middle Ages. Drawing heavily on manuscript evidence from the Cairo Genizah, the authors examine the challenges involved in the identification and interpretation of women's letters from medieval Egypt, the registers of women's written language, the relations between Jewish women and the Muslim legal system, the conversion of women, visions of women in Hell and gendered readings in the aggadic tradition of Judaism".